Reservoir properties and reactivity of the Faroe Islands Basalt Group : Investigating the potential for CO2 storage in the North Atlantic Igneous Province - Rosenqvist, Marija P.; Meakins, Max W.J.; Planke, Sverre; Millett, John M.; Kjøll, Hans Jørgen; Voigt, Martin J.; Jamtveit, Bjørn (International Journal of Greenhouse Gas Control, 2023)
Funding Information: We acknowledge funding from the University of Oslo through the Department of Geosciences, the European Research Council (ERC) through the ERC Advanced Grant Disequilibrium metamorphism of stressed lithosphere (DIME) (ERC-2015-AdG_669972), the Cambridge Arctic Shelf Program (CASP) through the Andrew Whitham CASP Fieldwork Awards 2020, and the Faculty of Mathematics and Natural Sciences at the University of Oslo through the project CO2Basalt. S. Planke acknowledges support from the Norwegian Research Council through center of Excellence funding to CEED (project no. 223272). H. J. Kjøll acknowledges AkerBP for funding through the project 8040 Paleocene. In addition, we thank the University of Iceland for covering the costs of the kinetic experiments. We would like to thank the Faroese Geological Survey (Jarðfeingi), Øyvind Hammer at the Museum of Natural History (Norway), Benjamin Bellwald at Volcanic Basin Energy Research (VBER), John Aiken from the Njord center, and Benoit Cordonnier from the European Synchrotron Radiation Facility (ESRF) in Grenoble, France, for their contributions to the project. Finally, we thank Sigurður Gíslason and the Carbfix team for providing laboratory facilities and assistance during part of this research. Funding Information: We acknowledge funding from the University of Oslo through the Department of Geosciences, the European Research Council (ERC) through the ERC Advanced Grant Disequilibrium metamorphism of stressed lithosphere (DIME) ( ERC-2015-AdG_669972 ), the Cambridge Arctic Shelf Program (CASP) through the Andrew Whitham CASP Fieldwork Awards 2020, and the Faculty of Mathematics and Natural Sciences at the University of Oslo through the project CO2Basalt. S. Planke acknowledges support from the Norwegian Research Council through center of Excellence funding to CEED (project no. 223272 ). H. J. Kjøll acknowledges AkerBP for funding through the project 8040 Paleocene. In addition, we thank the University of Iceland for covering the costs of the kinetic ...